Durability of the painted rendered facades, when introducing artificial acidic rain solution - Norvaišiene, Rosita; Burlingis, Arūnas; Stankevičius, Vytautas (Journal of Civil Engineering and Management, 2004)
The essential function of exterior walls is to provide a continuous barrier to the exterior environmental conditions. The decay of the building facades is accelerated by atmospheric pollution and acidic precipitation. For determining of the impact of atmospheric pollution on the building facade face materials, the tests examining the impact of the cyclic moisturing‐drying have been carried out with the use of acidic water solution to imitate acidic rain. The results of the experiments demonstrated that water solutions have greater destructive effects on the paint film by penetrating through it into the plaster base, thus forming new derivatives in it, which increase water absorption in the plaster base. In order to improve the standard testing on weather resistance of facing building materials, which does not ignore the impact of the atmospheric pollution, for localities where acidic precipitations are frequent, the climatic tests should also include the deteriorating effect of acidic water solutions on facing materials. The results of the experiments will be used for a creation of the prognostic method which will lead to the establishment of a new accelerated climatic ageing test cycle meant for determining a more reliable prognosis of the durability of materials.First Published Online: 14 Oct 2010